Results of surgical treatment for drug-resistant temporal epilepsy and related predictors of negative post-surgery outcome - O.A.M. Al-Sahli; L. M. Tibekina; A. E. Ivanova (Эпилепсия и пароксизмальные состояния, 2024)
Objective: to evaluate the results of surgical treatment and identify related predictors of unfavorable outcome in patients with temporal drug-resistant epilepsy (DRE) in long-term postoperative period.Material and methods. Fifty-one patients with temporal lobe DRE were examined using clinical, neuroimaging, electro- physiological, and laboratory research methods from June 2020 to June 2023. Anteromedial temporal lobectomy (AMLE) and selective amygdalohippocampectomy (SAHE) were performed in 38 (74.5%) and 13 (25.5%) cases, respectively. Postsurgery outcomes were evaluated in 51 patients 6 months later, continued in 43 and 20 patients 1 year and 2 years, respectively, afterwards.Results. The percentage of patients with significant improvement (Engel I/II) 6 months, 1 year and 2 years post-surgery was 82.4%, 72.1%, and 55.0%, respectively. After AMLE vs. SAHE, patients had a more favorable outcome while assessing seizure control. The predictors of unfavorable post-surgery outcome included a prolonged epilepsy course before surgery, the presence of electroencephalography-verified epileptiform activity in postoperative period, and repeated surgical intervention. Patient age, the presence of focal seizures evolving into bilateral tonic-clonic seizures as well as more frequent seizures before surgery were considered as potential predictors.Conclusion. The study results show that quite high effectiveness of seizure control in postoperative period in temporal DRE is quite high that may be accounted for by probability of removing epileptogenic foci and suppression of the mechanisms ensuring emergence and irritation of epileptic discharges. Nevertheless, effectiveness of surgical treatment fades off with time, which requires to further investigate the negative factors countering long-term post-surgery effect. In connection with this, a special attention should be paid to factors such as the presence of electroencephalography-verified epileptiform activity in postoperative period, repeated surgical intervention as well as prolonged epilepsy before surgery.